2012
DOI: 10.1021/jf3005614
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant Metabolism during Fruit Development of Different Acerola (Malpighia emarginata D.C) Clones

Abstract: The present research work describes the major changes in the antioxidant properties during development of acerola from five different clones. Ripening improved fruit physicochemical quality parameters; however, total vitamin C and total soluble phenols (TSP) contents declined during development, which resulted in a lower total antioxidant activity (TAA). Despite the decline in TSP, at ripening, the anthocyanin and yellow flavonoid content increased and was mainly constituted of cyanidin 3-rhamnoside and querce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
35
0
5

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(46 citation statements)
references
References 37 publications
6
35
0
5
Order By: Relevance
“…These results agree with the highest antioxidant activity in this stage. Behavior similar to X. americana was observed in fruits of acerola when studying the antioxidant metabolism of fruits, which found that the antioxidant activity, polyphenols, vitamin C and antioxidant enzymes showed higher values for the green fruits Oliveira et al (2012).…”
Section: Resultsmentioning
confidence: 65%
See 1 more Smart Citation
“…These results agree with the highest antioxidant activity in this stage. Behavior similar to X. americana was observed in fruits of acerola when studying the antioxidant metabolism of fruits, which found that the antioxidant activity, polyphenols, vitamin C and antioxidant enzymes showed higher values for the green fruits Oliveira et al (2012).…”
Section: Resultsmentioning
confidence: 65%
“…The higher antioxidant activity for green fruits was also observed in fruits of Malpighia emarginata (Oliveira, Moura, Brito, Mamede, & Miranda, 2012). The X. americana presents antioxidant activity similar to fruits with considerable amounts of antioxidants such as Myrciaria dubia (478 g fruit/g DPPH Å and 153 lmol Trolox/g), Mouriri pusa (414 g fruit/g DPPH Å and 125 lmol Trolox/g) and Malpighia emarginata (670 g fruit/g DPPH Å and 96.6 lmol Trolox/g) (Rufino et al, 2010).…”
Section: Resultsmentioning
confidence: 76%
“…Oliveira et al (2012), who evaluated the fruit of five acerola clones at different stages of maturation, reported that the ripe fruit had average values of titratable acidity ranging from 1.24 to 1.81% malic acid, and a pH ranging from 3.38 to 3 50. These results are within the range seen in the present study.…”
Section: Resultsmentioning
confidence: 99%
“…Also in acerola, six commercial clones were investigated by Sampaio et al [37], who found that the clone II 47/1 had the highest anthocyanin content. Oliveira et al [38], studying five acerola clones, established that clones II 47/1, BRS 237, and BRS 236 presented outstanding results for vitamin C, phenols and antioxidant enzyme activity.…”
Section: Methods For Improving Plant Phenolic Contentmentioning
confidence: 99%